(3OjhGf TPhQ GdPgHs - (3Ydj Hf ehSi Hf Ydj, CHh GdMSf, GHf CQaY QCSg GdCfUGQj GdCfOdSj GdLjGfj,J (B593 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI bGd GdTjN GdGeGe GdYGde GdYdGeI CHh GdMSf Ydi Hf GHj GdbGSe Hf Ydi GdGfUGQj GdGfOdSj GdeYQha HGHf GQaY QCS YaG Gddg Yfg s
(3BNQgG (B:s
(3aEf cfJ aj Md GdQehR eOGjfG GNGfG abO fdJ GdPj cfJ QGLjkG hEdG adG JQJY HgPG agj QhVI bO GeJdCJ ddQGFOjf GaGYjG JeQMjhGf GdTPhQ s
(3Vef eLehY , JQJjHgG (B: 1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B249s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs